The organizational response to persons with mental illness involved with the criminal justice system - Hartwell, Stephanie W. (Amsterdam ; Oxford : Elsevier JAI, 2005)
From arrest to release, the organizational response to mentally ill offenders is continually evolving according to existing policies and resources. How organizations respond, how they should respond, and their ability to evolve is important. The chapters in this volume offer cases with wide ranging policy implications regarding structural and functional changes institutions and organizations might consider given the confines of context and resources to improve the conditions of mentally ill offenders. Policies regarding mentally ill offenders are played out differently by state and county, and the capacity of communities to support individuals with mental illness and criminal histories varies. The quantitative and qualitative research on organizational responses to offenders with mental illness highlighted herein include program evaluation; data collection; best practices in resource utilization; dispositions and the courts; screening; and a broader articulation of outcomes given the special needs of the population.
pt. 1. Programming and program evaluation -- two cases from Massachusetts. A public health approach to address the mental needs of juvenile offenders / Robert A. McMacking and Elliot Pittel -- E pluribus unum: creatind a multi--organizational structure for serving arrestees with serious mental illness / Jonathan C. Clayfield ... [et al.] -- pt. 2. Risk assessment--two cases from around the globe. Rambo: the evaluation of an intervention program for UK mentally abnormal young offenders / Theodore I. Mutale -- Risk assessment and violent recidivism risk management in convicts from Argentina / Jorge O. Folino -- pt. 3. Mitigating circumstances--two cases from the courts. Offender ethnicity and juvenile court referrals to substance abuse services / Carolyn S. Breda -- Benefits and risk of using "diminished capacity" mitigation in death penalty proceedings / Beth Bjerregaard ... [et al.] -- pt. 4. Prisons--two cases on identification and treatment of mentally ill offenders behind bars / James A. Swartz and Arthur J. Lurigio -- The impact of a residential treatment unit on the prison adjustment of mentally disordered inmates / Christine Gagliardi -- pt. 5. Assessing outcomes--two studies examining outcomes of ex--offenders with mental illness. Beyond recidivism: identifying additional measures of success for special offenders programs / Anne Marie Cote and Kimberly A. Mahaffy -- The organizational response to community re--entry / Stephanie W. Hartwell.
Description based on print version record.
Keywords: Mentally ill offenders; Justice, Administration of; Organizational behavior; Offenders; Mental health services; Political Science -- Political Freedom & Security -- Law Enforcement; Psychology -- Mental Illness